A neoeugenics in the collapse of health in pandemic Brazil from the biopolitical perspective (Research, Society and Development, 2022)
The objective of this paper was to reflect on the presence of some eugenic signs being applied involuntarily, throughout the pandemic, by doctors and health professionals according to a biopolitical perspective. Eugenics can also be defined as a Science or method of human selection based mainly on biological premises and not related to religious incomprehension or clashes of a political-economic domination system. The COVID-19 pandemic is located in the national context under the biopolitical perspective and state racism, Foucaultian concepts. Health professionals faced many challenges during the health crisis, especially with regard to the choices they were forced to make, given that at certain times the health system collapsed in the country. We reflect on whether this choice of health professionals would be a new reading of eugenics in the pandemic context.